Brightening of long, polymer-wrapped carbon nanotubes by sp3 functionalization in organic solvents - Berger, Felix J.; Lüttgens, Jan; Nowack, Tim; Kutsch, Tobias; Lindenthal, Sebastian; Kistner, Lucas; Müller, Christine C.; Bongartz, Lukas; Lumsargis, Victoria A.; Zakharko, Yuriy; Zaumseil, Jana (ACS nano, 2019)
The functionalization of semiconducting single-walled carbon nanotubes (SWNTs) with sp3 defects that act as luminescent exciton traps is a powerful means to enhance their photoluminescence quantum yield (PLQY) and to add optical properties. However, the synthetic methods employed to introduce these defects are currently limited to aqueous dispersions of surfactant-coated SWNTs, often with short tube lengths, residual metallic nanotubes, and poor film-formation properties. In contrast to that, dispersions of polymer-wrapped SWNTs in organic solvents feature unrivaled purity, higher PLQY, and are easily processed into thin films for device applications. Here, we introduce a simple and scalable phase-transfer method to solubilize diazonium salts in organic nonhalogenated solvents for the controlled reaction with polymer-wrapped SWNTs to create luminescent aryl defects. Absolute PLQY measurements are applied to reliably quantify the defect-induced brightening. The optimization of defect density and trap depth results in PLQYs of up to 4% with 90% of photons emitted through the defect channel. We further reveal the strong impact of initial SWNT quality and length on the relative brightening by sp3 defects. The efficient and simple production of large quantities of defect-tailored polymer-sorted SWNTs enables aerosol-jet printing and spin-coating of thin films with bright and nearly reabsorption-free defect emission, which are desired for carbon nanotube-based near-infrared light-emitting devices.
Gesehen am 29.04.2020